The Power of Information : The Impact of Mobile Phones on Farmers’ Welfare in the Philippines - Labonne, Julien (2012)
The authors explore the impact of access to information on poor farmers consumption. The analysis combines spatially coded data on mobile phone coverage with household panel data on farmers from some of the poorest areas of the Philippines. Both the ordinary least squares and instrumental variable estimates indicate that purchasing a mobile phone has a large, positive impact on the household-level growth rate of per capita consumption. Estimates range from 11 to 17 percent, depending on the sample and the specification chosen. The authors perform a range of reliability tests, the results of which all suggest that the instruments are valid. They also present evidence consistent with the argument that easier access to information allows farmers to strike better price deals within their existing trading relationships and to make better choices in terms of where they choose to sell their goods.